Overexpression of CircRNA BCRC4 Regulates Cell Apoptosis and MicroRNA-101/EZH2 Signaling in Bladder Cancer - 李博;谢飞;郑福鑫;蒋国松;曾甫清;肖行远 (Current medical science, 2017)
Emerging evidence has indicated that circular RNAs（circRNAs） play pivotal roles in the regulation of cellular processes and are found to be aberrantly expressed in a variety of tumors. However, the clinical role of circ RNAs in bladder cancer（BC） and the molecular mechanisms have yet to be fully understood. In this study, the clinical specimens were obtained and the expression level of a circ RNA BCRC4 was detected by real-time PCR in both BC tissues and cell line. The circular RNA over-expression plasmid was constructed and transfected into BC cells and related cell line. The cell cycles and apoptosis were observed using inverted microscope and flow cytometry. Western blotting was used to compare the relative protein expression of groups with different treatments. It was found that circ RNA BCRC4 expression was lower in BC tissues than in adjacent normal tissues. Furthermore, consequences of forced-expression of BCRC4 promoted apoptosis and inhibited viability of T24T and UMUC3 cells, and up-regulated BCRC4-increased miR-101 level, which suppressed EZH2 expression in both RNA and protein levels. In addition, gambogic acid（GA） is a promising natural anticancer compound for BC therapy, and GA treatment increased the BCRC4 expression in T24T and UMUC3 cells in a dose-dependent manner. Altogether, our findings suggest that BCRC4 functions as a tumor suppressor in BC, and mediates anticancer function, at least in part, by up-regulating the expression of miR-101. Targeting this newly identified circ RNA may help us develop a novel strategy for treating human BC.